Profil Usaha Mikro Kecil Dan Menengah Kecamatan Kota Waingapu - Tumpal Pangihutan Situmorang (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2013)
Knowingly or not the micro, small and medium enterprises have the potential and prospects to be developed, in terms of the characteristics, that is, the scale of business, number of employees, capacity and sales is very different from big enterprises, therefore, it can be said that the small and medium enterprises have a toughness and resilience in business continuity. This study emphasizes the entrepreneurial profile in Waingapu district which examines the type of bussiness, labor, education, type of work, bussiness license, marketing, technology used and how to obtain the raw materials and the obstacles dealth by entrepreneurs.The population of this study is all the UMKM in district Kota Waingapu which consists of 4 sub-districts: Matawai, Kamalaputi, Hambala and Kambajawa. While, the sample is the UMKM in 4 sub-districts based on the population data in RT where all the businesses located, whereas the data analysis uses descriptive technique in which presentation in the form of cross-tabulation.Results of this study conclude that all the bussiness in district Kota Waingapu are small and micro bussiness with various background education, elementary schools to high schools. The entrepreneurs are mostly dominated by men, the entrepreneurship motivation are their own initiatives, as a source of additional income and while others are to continue the work of their parents and the rests have no other choice jobs, while the origin of the raw materials and marketing are in and out of districts, regencies and provinces. The obstacles of entrepreneurships are mostly about the capitals, simple financial records as well as the lack of skilled labor.Keyword: Entrepreneurship, Micro, Small and Medium Enterprises